Assessment of red-edge vegetation descriptors in a modified water cloud model for forward modelling using Sentinel–1A and Sentinel–2 satellite data - Yadav V.P.; Prasad R.; Bala R.; Srivastava P.K. (My University, 2025)
This study investigates the potential of different vegetation descriptors (V) in the modified water cloud model (MWCM), with a focus on comparing the Red–Edge vegetation indices (VI) based and other vegetation descriptors using Sentinel–1A and Sentinel − 2 satellite data. In order to reduce the influences of vegetation and roughness effectively, a soil geometrical model of equivalent roughness was coupled with a MWCM for the simulation in forward modelling. The optimum value of vegetation extinction coefficient (K VI) and dense vegetation indices ((Formula presented.)) of modified Beer’s law were calculated using non-linear least square optimization technique. After the parameterization of MWCM, the five different types of V for wheat crop were tested for the simulation of backscattering coefficients ((Formula presented.)) at VV polarization. The higher statistical performance indices like coefficient of determination (R2  = 0.96), root-mean-square error (RMSE = 0.17 (dB)) and Nash sutcliffe efficiency (NSE = 0.93) were found for the case of Red-Edge-based vegetation descriptors (for VI = NDVIRE) than others in MWCM. Therefore, this methodology reveals that the VI = NDVIRE by modified Beer’s law can be used effectively as the vegetation parameter in the MWCM for accurate simulation in forward direction over vegetation-covered areas. © 2020 Informa UK Limited, trading as Taylor & Francis Group.